(3OhQ GdgjFI GdYGeI ddQbGHI GdeGdjI aj GdQbGHI Ydi JOGhd GdChQGb GdeGdjI (B: s (3OQGSI ebGQfI eY GdfXGe GdCeQjcj (B/ s - (3eMeO ESeGYjd gGTe Ydjs; (3Ydi SjO bGSe s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3JfGhd gPG GdHMK GdJYQja HGdCShGb GdeGdjI(B: (3h CShGb JOGhd GdChQGb GdeGdjI(B: (3h CgejJgG(B: (3h OhQI GdQbGHI YdjgG(B: (3h YQV ddfXe GdbGfhfjI ddJOGhd h GdgjFI GdQbGHjI ai cd ef GdfXGejf GdeUQj h GdCeQjcj(B: (3ceG JfGhd WQb GdQbGHI Ydi cd ef GdHhQUI(B: (3h TQcGJ GdSeSQI(B: (3h TQcI GdEjOGY h GdbjO GdeQcRi(B: (3HGYJHGQgG GdLgGJ GdeTGQcI ai EJeGe YedjGJ GdJOGhd(B: (3h cPdc WQb GdQbGHI Ydi YedjGJ GdJOGhd PGJgG(B: (3ddJCcO ef NdhgG ef GdZT Ch GdGMJjGd Ch GdJdGYH h Pdc ai VhA GdbhGfjf GdSGQjI ai cd ef eUQ h GdhdGjGJ GdeJMOI GdCeQjcjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2011s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B531547s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdQbGHI Ydi JOGhd GdChQGb GdeGdjIs; (3GdfXGe GdCeQjcjs; (3GdgjFI GdYGeI ddQbGHI GdeGdjIs; (3HhQUg GdGhQGb GdeGdjg s; (3eHOG MQjg GdJOGhd s; (3fbd edcjg GdGhQGb GdeGdjgs; (3GShGb GdJOGhd ai eUQ s; (3GShGb GdJOGhd ai GeQjcG s; (3WQb GdQbGHg Ydi GShGb GdJOGhds; (3GdbGfhf GdGeQjci s; (3GfhGY GdQbGHg s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs